A checklist of the millipedes (Diplopoda) of Cambodia - Likhitrakarn, Natdanai; Golovatch, Sergei I.; Panha, Somsak (Zootaxa, 2015)
At the present, the millipede fauna of Cambodia comprises only 19 species from 15 genera, 12 families and 8 orders. These counts certainly represent but a minor fraction of the country’s real diversity of Diplopoda even at the ordinal level, let alone at lower ones. Based on the available information from the adjacent parts of China, Thailand, Myanmar, Vietnam and/or Laos, the orders Glomerida, Platydesmida, Polyzoniida, Callipodida and Chordeumatida must occur in Cambodia, maybe also Stemmiulida and Siphonocryptida, but none has been recorded there yet. This shows that a lot more collecting effort is required to amass a representative material of Diplopoda of Cambodia to make it available for study.